Pendampingan Kemandirian Ekonomi Kerakyatan melalui Program Pembuatan Pakan Alternatif Berbahan Baku Ampas Tahu dan Daun Talas pada Komunitas Budidaya Ikan Gurame di Metro Utara Kota Metro - Subandi Subandi; Nur Asiyah; Ida Fiteriani; Mispani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
Metro has a unit of business more than 99% in the small and medium micro-industry sector, including the type of fresh fish water production. Metro city produces fish ponds of 2,122.01 tons per-year in two sub-districts, namely north metro and central metro. The monitoring community activity is aiming to utilize the organized community. The community owns assets to materialize the independence of the economy through cultication of fish carp manufacture of feed alternatives program made from raw pulp out and taro leaf. The monitoring use ABCD (asset-based community development), so it can develop owned assets community aquaculture fish-arp to be self-sufficient in the economy and increase the social welfare. Results are strengthening of the aquaculture fish-carp capacity skills of the manufacture of alternatives feed and generate prosperity economics community.